THE ROLE OF CIVIL RELIGION FORMING CIVIL SOCIETY THROUGH PRACTICING RELIGIOUS COMMENT - Agus Salim Nst (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Modern society requires the new symbol rituals development to create a solidarity in a pluralistic country such Indonesia. This is what sociologists called civil religion. Andrew Shauks stated that civil religion is not a true religion as existing religious practices; it did not compete with conventional traditions, but it is existing on it and break it bonds. The same idea also explained by Olaf Schuman that civil religion is not a religious source for someone where he gained his understanding of the identity and social obligations. It remains a resource is the existence of religion civil religion should not and could not be a substitute powerless religions. Civil religion is not like a religion and not a rival to the existing religions. Rather it part, it exist of religions and values and norms generated by them to ensure a life together that is sustainable and harmony in an pluralistic society situation to create society (civil society), an open society, egalitarian, and tolerant based on ethical values, moral transdental